Bracket Creep Revisited: Progressivity and a Solution by Adjusting the Rich Tax in Germany - Ismael Martin Flores Unzaga; Junyi Zhu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the redistributive and revenue effects of bracket creep in Germany under various inflation scenarios and evaluates the feasibility to charge a rich tax to fight bracket creep for the income distribution in 2009. Using a tax micro-simulation model developed for the newly available PHF data, we document an inverted U-shaped overall redistribution effect of the tax system with respect to the inflation rate, which contrasts Immervoll (2005) who finds that the fiscal drag always enhances the equalizing property. Delaying indexation might not be better off in terms of inequality. A politically in-between approach is proposed to raise the marginal tax rate for the top bracket to compensate the government revenue loss due to indexing the tax schedule in Germany. The rich tax required for fully financing the indexation can be sizable. Under our simulation environment, this rate can reach above 75% with four years' inaction on 4% annual inflation. When this rich tax can be fiscally possible, it can totally offset the decrease of global redistribution effect from indexation. Our results echo the inequality indexing proposed by Burman, Shiller, Leiserson, Rohaly and Kennedy (2007) by suggesting institutionalizing a joint adjustment of rich tax and bracket creep / inflation indexing which justifies a pro-growth, risk reducing, revenue-neutral and framing effective policy.
Keywords: C81; H24; D31; H23; 330; Inflation; Fiscal Drag; Rich Tax; Progressivity of Income Tax; Income Distribution; Micro-simulation; Inequality Indexation; Inflation; Progressive taxation; Income distribution; Simulation